Self-reported health in the Republic of Karelia, Russia and in North Karelia, Finland in 1992 - HEISTARO, SAMI; LAATIKAINEN, TIINA; VARTIAINEN, ERKKI; PUSKA, PEKKA; ANTTIUUTELA; POKUSAJEVA, SVETLANA; UHANOV, MIHAIL (The European Journal of Public Health, 2001)
Background: Major differences in mortality, cardiovascular disease risk factors and health behaviour are known to exist between the populations of eastern Finland and the Republic of Karelia, Russia. Little is known, however, whether similar differences exist in subjective health. Methods: In spring 1992 a population survey was conducted in North Karelia, Finland and in the area of Pitkäranta, Republic of Karelia, Russia. Random population samples (n=2,000 in North Karelia and n=1,000 in Pitkäranta) stratified for age and sex were taken from the population registers. The subjects completed questionnaires and were examined at local health centres. Results: In North Karelia 50% of men reported their health as being quite good or very good, compared to 34% in Pitkäranta (p<0.0001 for area difference). Among women the corresponding percentages were 58% in North Karelia and 22% In Pitkäranta (p<0.0001). High household income and education were associated with good self-rated health among both sexes in North Karelia and among women but not men in Pitkäranta. Self-reported physical condition was better in North Karell than in Pitkāaranta (p<0.0001). Psychosomatic symptoms (p=0.0002 among men and p<0.0001 among women) and many somatic symptoms were more prevalent in Pitkäranta than in North Karelia. Conclusion: In general, people In North Karelia, Finland feel healthier than people in the neighbouring Republic of Karelia, Russia. Socioeconomic differences in subjective health are less prominent in the Republic of Karelia.